Geochemical characterisation of northern Norwegian fjord surface sediments: A baseline for further paleo-environmental investigations. (15th September 2017) - Faust, Johan C.; Scheiber, Thomas; Fabian, Karl; Vogt, Christoph; Knies, Jochen
Abstract: Norwegian fjord sediments are promising archives for very high resolution records of past environmental changes. Recent investigations of the modern depositional environment within fjords revealed that the accurate quantification of the inputs, sources, and sedimentary preservation of organic and inorganic material is crucial to decipher long term past climate signals in the sedimentary record of a certain fjord. Here, we investigate the elemental composition, bulk mineral assemblage and grain size distribution of forty-one surface sediment samples from a northern Norwegian fjord system. We reveal modern geochemical and sedimentological processes that occur within the Vestfjord, Ofotfjord and Tysfjord. Our results indicate a very heterogeneous sediment supply and intricate sedimentation processes. We propose that this is related to the complex fjord bathymetry, a low hydrodynamic energy environment, differences in the hinterland bedrock composition and a relatively small drainage area causing a rather diffuse freshwater inflow. Moreover, we show that marine carbonate productivity is the main calcite and Ca source in all three fjords. Highlights: Element distribution in fjord sediments is not necessarily related to a specific grain size fraction or mineral. Ca/Al and calcite are good indicators for marine carbonate productivity versus terrigenous sediment supply in fjords. Fjord sediment compositions can vary considerably even over very short distances if major river outlets are absent. Differences in bathymetry and the hydrodynamic energy can cause different sedimentary regimes for each Norwegian fjord.